Kinetic Study of Supercritical Water Gasification of cellulose from Biomass - Chico, Sebastian; Romero, Michelle; Chulde Ch., Diego V.; Narváez C., Ricardo A. (EASI: Engineering and Applied Sciences in Industry, 2025)
This work carried out the supercritical gasification of cellulose in water (SCWG). The products obtained from the reaction were measured and their kinetic parameters were determined. The SCWG of cellulose was carried out in a supercritical PFR reactor evaluating three reaction temperatures: 372 °C, 374 °C, 376 °C for a reaction time of 15 min. The reaction products were analyzed by gravimetry, liquid chromatography HPLC and gas chromatography. The kinetic parameters of the SCWG reaction were then determined. This reaction produces hydrogen, with high energy potential, and lactic acid, a high-value product. The results show that, by raising the temperature of cellulose from subcritical to supercritical, the production of both compounds increases, reaching its highest concentration at a temperature of 376 °C and pressure of 3300 psi. To determine the kinetic parameters, integrated equations were used, revealing that the SCWG reaction follows first-order kinetics under the analyzed operating conditions. and its kinetic constants for each temperature are: k1=0.01386 〖min〗^(-1), k2= 0.01538 〖min〗^(-1) and k3=0.01529 〖min〗^(-1). This study advances the understanding of supercritical gasification as an alternative to convert waste into valuable products.